"Reanalysis and Analogy”: Some Syntactic Mechanisms Influencing the Grammaticalization Process in the Thai Language - Khotchaphet, Suwatchai; Sathitphong , Pattamaphon; Kaewnoi, Surasak (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This article discusses the syntactic mechanisms that lead to the process of grammaticalization, focusing on two key mechanisms: reanalysis and analogy. Reanalysis refers to changes that result in the creation of new structures, replacing the old ones. These changes, which occur at a deep, often invisible level, are referred to as "covert" changes. On the other hand, analogy involves the transformation of one linguistic form based on another, resulting in changes at the surface level of language, which are more apparent and thus termed "overt" changes. The grammaticalization process requires the reanalysis of content words, such as nouns and verbs, as well as the reanalysis of syntactic units. The outcome of this reanalysis is that content words become grammatical words. These grammatical words are then able to combine with various other words, a flexibility not present when they function solely as content words. Therefore, the mechanism that allows grammatical words to combine with other words is analogy.